Epigenetic silencing of Lgr5 induces senescence of intestinal epithelial organoids during the process of aging - Ryoei Uchida (Nature Portfolio, 2018)
Epigenetic silencing of Lgr5 in aged organoids To understand the molecular features underlying stem cell aging, we established intestinal epithelial organoids derived from both young and aged mice, and investigated alterations in their senescence and epigenetic status. Senescence-related changes including accumulation of senescence-associated β-galactosidase were observed in intestinal epithelial organoids derived from aged mice. We also demonstrated that the important stem cell marker Lgr5 was epigenetically silenced by trimethylation of histone H3 lysine 27, inducing suppression of Wnt signaling and a decrease of cell proliferation in organoids from aged mice. Our results suggest that organoids derived from aged animals could be a powerful research tool for investigating the molecular mechanisms underlying stem cell aging and for development of some form of anti-aging intervention, thus contributing to prolongation of healthy life expectancy.